Spectral response of 4 vegetation types during 2009-2010 occurrence of moderate El Nino Southern oscillation in Cagayan river basin - Montoya, Cristina M. (2017)
An usual warming of sea surface temperature (SST) along the equatorial Pacific was established in June 2009 to June 2010 which developed weak to moderate El Nino Southern Oscillation (ENSO). Time series vegetation indices of 4 vegetative covers derived from Moderate Resolution Imaging Spectroaradiometer (MODIS) sensors were used to understand the effects of El Niño in Cagayan River Basin. The research process used in this study can serve as a guide for vegetation assessment and monitoring, particularly during an El Niño event, for timely crop assessment and monitoring.

In general, the spectral mean test for 4 vegetation categories, namely, forest, agricultural crops, grassland, and woody plants showed that during ENSO years, vegetation index was lower, as shown by a lower mean Enhanced Vegetation Index (EVI) for 3 out of the 4 categories. Only forest areas do not seem to be significantly affected by the El Niño phenomenon. Grassland was the most affected during the ENSO study period. Woody plants such as shrubs and perennial trees were evidently affected by El Niño. Comparison of results based on T-test (at 95% confidence interval) showed that EVI was more accurate in determining the effect of drought to vegetation compared to Normalized Difference Vegetation Index (NDVI). In general, the impact of El Niño to the 4 vegetation categories is more pronounced during summer season since there was adverse dry spell compared to non-summer months.
Keywords: Remote sensing